Preparation of biodiesel from waste cooking oil and refines bleached deodorized oil using single step batch transesterification process with the aid of KOH as the catalyst - Mahfuzah, Mansor (2009)
Biodiesel is a cleaner burning diesel replacement fuel processed from natural, renewable derived from biological sources such as waste cooking oil and refined bleached deodorized palm oil. The type of process that needs to be done to produce biodiesel is called transesterification. The transesterification of waste cooking oil and refined bleached deodorized palm oil with short-chain alcohols, in the presence of base-catalyst potassium hydroxide (KOH) and methanol as solvent, by means of single step batch transesterification process in order to obtain biodiesel fuel was studied. The reaction has been done in water bath. The process variables that been investigated are catalyst concentration and reaction time. The variables that are fixed throughout the whole experiment were molar ratio of methanol to raw oil with 6: 1, reaction temperature at 40oC and mixing degree of mechanical stirrer at 1300 rpm. This paper also studied the combustion characteristic which is the carbon monoxide emission between WCO and RBD to be compared with conventional diesel, and determined the optimal transesterification reaction conditions that produce the maximum methyl ester content or purity and biodiesel yield. The best result for highest yield and highest purity is at 60 minutes reaction time and using 1.5% catalyst concentration.